O perfil das indústrias de alimentos do estado de Sergipe : relevância da produção e seu impacto no território local - Silva, Anderson Rosa da (2016)
The industrial sector is an activity of great contribution for the local economic development. Given this reality, the present research structured, with the aim to trace and to diagnose the profile of food industries in the state of Sergipe, through the observance of the degree of development, innovation and its economic impact in the local territory. The collected data extracted of made available information online, through the website of each industry and searched institution, beyond a bibliographical revision in periodic articles, books and that approach the explored subject. The evolution of the food industries contextualized in the course of time, as well as the evolution in the consumption of the products industrialized for society.Taking in consideration the impact of the innovation and Law 10,973 (Law of the Innovation), of 02.12.2004, discussed the importance and relevance of the innovation and the enterprising spirit for the development of a company or industry, and how much the management of the Copyright provides the progress of the company, through the protection of the innovations, making possible to increase the competitiveness of the company and to ahead obtain strategic advantages of the market. From this discussion, the profile of food industries in the sergipano territory traced, identifying the scene current based of the production and lines of products of main industries. It was accomplish in such a way mapping of Food Industries, how much the mapping of the Institutions of Higher education, in the perspective to make a correlation, proving the contribution of the IES in the training of hand of qualified work for industries. The amount of products of searched industries and the material used for confection of the packages, given raised that they more make possible the comparative degree and the comment of developed industries. Finally, through System FIRJAN, in 2013, it identified to the amount of professionals of the area of Engineering of Foods and courses similar that act in the places where it has concentration of industries, which ahead showed a low index of an important number of industries. With regard to the area of Engineering of Production, Quality, Security and similar courses, the number of professionals is satisfactory. The similar area of Chemical Engineering and courses presents the biggest number of professionals, presenting a good index; therefore, this area is of utmost importance for the attainment of healthy products and good quality. Finally, the state of Sergipe provides of a good number of food industries, of innovatory and competitive products in the market, being that some industries known abroad due to the quality and capacity of exporting their products.